STRATEGI KOALISI PARTAI POLITIK DALAM PEMENANGAN PASANGAN ZULKIFLI AS DAN EKO SUHARJO PADA PEMILUKADA DI KOTA DUMAI TAHUN 2015 - Rhesty Sundari Fauziah; M. Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aims to determine what strategies are used by the Coalition of Political Parties in the winning pair Zulkifli AS and Eko Suharjo at the General Election in Kota Dumai 2015. This study is an analysis of the offensive strategy (attack) and defensive strategies (last) used by the coalition of political parties supporting the Zulkifli AS and Eko Suharjo in Kota Dumai Election 2015. This research was conducted during a three -month high of May until the month of July 2016 in Kota Dumai precisely in Dumai Care Coalition Team Post Office and Branch Council (DPC) each Party Coalition. This study uses qualitative research is research that is descriptive and tend to use the analysis and based on the theoretical basis as a guide so that the focus of research in accordance with the fact the field. Data analysis techniques to analyze data is the data obtained and set forth in writing and developed through the theory to obtain a conclusion in accordance with the purpose of research.Research shows that the coalition parties supporting the pair Zulkifli US and Eko Suharjo has implemented several political strategy for pemengan at the General Election in Kota Dumai 2015 were divided into Strategic Offensive and Defensive Strategies.Keyword: Strategy, Coalition, Election.